Electron transfer behavior of pincer-type {RhNO}8 complexes: Spectroscopic characterization and reactivity of paramagnetic {RhNO}9 complexes - Pellegrino, Juan (2013)
The electrochemistry of the {RhNO}8 complexes [Rh(PCPtBu)(NO)][BF4] (1+), [Rh(PCPtBuCH2)(NO)][BF4] (2+), and Rh(PCPtBu)(NO)Cl (3) was studied. Both four-coordinate complexes 1+ and 2+ exhibit a reversible reduction within the CH2Cl2 solvent window. Nevertheless, the chemical or electrochemical reduction of 1+ and 2+ in CH2Cl2 led to the formation of the five- coordinate {RhNO}8 complexes 3 and Rh(PCPtBuCH2)(NO)Cl (4), respectively, through chloride abstraction from CH2Cl2 by the one-electron-reduced {RhNO}9 species [Rh(PCPtBu)(NO)]• (1•) and [Rh(PCPtBuCH2)(NO)]• (2•), as has been observed for many other 17-electron paramagnetic complexes. The new complex 4 was fully characterized by multinuclear NMR techniques, IR, X-ray diffraction, CV, UV−vis, and elemental analysis. On the other hand, the five-coordinate complexes 3 and 4 show only one irreversible oxidation in CH2Cl2 and two irreversible reductions in THF. The {RhNO}9 complex 1• could be obtained quantitatively by one-electron reduction of 1+ with cobaltocene in nonchlorinated solvents and was characterized by IR, EPR, and 1H NMR in solution. Activation of carbon−halogen bonds by complex 1• was observed by studying the reactivity of 1• with some aryl halides, giving in all cases the {RhNO}8 Rh(PCPtBu)(NO)X (X = Cl−, 3, or X = I−, 6) as the only rhodium complex, while a complex with coordination of the aryl moiety was not observed as a stable final product in any case. The fate of the aryl organic radicals could be determined in some cases. In addition, DFT calculations were performed to elucidate the electronic structure of 1• and to support the observed reactivity.